An introduction to financial markets : a quantitative approach - Brandimarte, Paolo (New J, 2018)
Covers the funddamental topics in mathematics, statistics, and financial mangement that are required for a thoriugh study of fianncial markets.This comprehensive yet accessible book introduces students to financial markets and delves into more advanced material at a steady pace while providing motivating examples, poignant remarks, counterexamples, ideological clashes, and intuitive traps throughout. Tempered by real-life cases and actual market structures
Keywords: Business and Economics; Finance